Type IV longus pilus of enterotoxigenic Escherichia coli: occurrence and association with toxin types and colonization factors among strains isolated in Argentina - Pichel, Mariana (2002)
Fil: Pichel, Mariana G. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.